2005
DOI: 10.4049/jimmunol.175.10.6924
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Inflammation: Prostaglandin E2 Dissociates Nuclear Trafficking of Individual NF-κB Subunits (p65, p50) in Stimulated Rheumatoid Synovial Fibroblasts

Abstract: NF-κB transcription factors regulate inflammatory responses to cytokines such as IL-1β and TNF-α. We tested whether PGE2 regulated nuclear localization of individual NF-κB subunits, p65 and p50, in synovial fibroblasts harvested from patients with rheumatoid arthritis (RA). IL-1β/TNF-α stimulated the translocation of p65 and p50 from the cytosol to the nucleus of human RA synovial fibroblasts, as well as NF-κB activation measured by luciferase reporter assay. PGE2 (10 nM, 6 h) enhanced p50, but inhibited p65 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0
4

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 39 publications
3
96
0
4
Order By: Relevance
“…Consistent with our observations, PGE 2 /EP4-mediated inhibition of stimulus-induced MEK activation occurs in other cell types (45)(46)(47). We furnish here novel evidence supporting the involvement of EP4-EPRAP signaling in the suppression of MEK activation through inhibiting inducible p105 phosphorylation and degradation.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Consistent with our observations, PGE 2 /EP4-mediated inhibition of stimulus-induced MEK activation occurs in other cell types (45)(46)(47). We furnish here novel evidence supporting the involvement of EP4-EPRAP signaling in the suppression of MEK activation through inhibiting inducible p105 phosphorylation and degradation.…”
Section: Discussionsupporting
confidence: 80%
“…Although the effect of PGE 2 or EP4 signaling on NF-B activation probably varies by cell type (51), previous studies demonstrated that PGE 2 and EP4 signaling suppressed NF-B DNA binding activities in various inflammatory cells (46,52,53).…”
Section: Discussionmentioning
confidence: 99%
“…tained from patients at the time of total joint arthroplasty, as previously described (44). The collection and use of human RASFs and OASFs were reviewed and approved by the Institutional Board of Research Associates, New York University School of Medicine (New York, NY).…”
Section: Results Fti-276 But Not Statins Inhibited Rasf Secretion mentioning
confidence: 99%
“…Paradoxically, PGE 2 has also been demonstrated to have antiinflammatory roles in various animal models [10,11]. The dichotomous role of PGE 2 in inflammation is underscored by in vitro findings showing that its effects on cytokine/chemokine release can be pro-inflammatory [12,13] or anti-inflammatory [14][15][16], depending on the system. Similar to PGE 2 , the cytokine IFN-c has also been shown to have dual, apparently contradictory, roles in inflammation (as recently reviewed in ref.…”
Section: Introductionmentioning
confidence: 94%